Immunohistochemistry assay of osteocalcin on bone healing with CHA-10% propolis - Sri P. Lastianny; Ayuda N. Sukmawati; Al SK. Soesilowati (DiscoverSys Inc., 2022)
Objective: To evaluate the effect of the application of carbonated hydroxyapatite-propolis 10% on open flap debridement towards osteocalcin expression of periodontitis induced Oryctolagus cuniculus. Material and Methods: Six rabbits (Oryctolagus cuniculus) were divided into three groups, which are carbonated hydroxyapatite-propolis 10% group, carbonated hydroxyapatite group, and open flap debridement group. Periodontitis on animal models was inducted with a combined technique using ligation and LPS injection of P.gingivalis. On each group, the animals were decapitated on day 7 and day 14 after the designated treatment. The immunohistochemistry assay was used to measure the osteocalcin expression. The data were analyzed statistically with Two Way Anova and continued with post hoc LSD. Results: The results showed that the carbonated hydroxyapatite-propolis 10% group had the highest osteocalcin expression on day 7, followed by carbonated hydroxyapatite group and the open flap debridement group (p<0,05). There was no significant difference in the expression of osteocalcin on day 7 and day 14 (p>0,05) on the carbonated hydroxyapatite-10% propolis group. Conclusion: The application of carbonated hydroxyapatite-propolis 10% could increase the osteocalcin expression on periodontitis induced Oryctolagus cuniculus.